Comparison of Different PWM Techniques in T-Source Inverter - Rama Rajeswari, T.; Hemaprabha, G.; T. Rajesh; P. Sivaraman (Asian Journal of Electrical Sciences, 2015)
This paper deals with the analysis of three phase Tsource inverter by using different control techniques to minimize the switching losses. T-source impedance network is developed to overcome the drawbacks of Z-source inverter. TSource inverter has low reactive components in comparing with ZSI. The Total harmonic distortion (THD) of output voltage for both the control methods has been analyzed by using FFT analysis. The maximum constant boost pulse width modulation (PWM) control method has more voltage gain and less voltage stress compared to other techniques. The experiments are done and the results are shown for capacitor voltage, load current and load line voltage for simple boost, constant boost control technique and space vector modulation PWM techniques are presented using MATLAB/Simulink.